Implementasi Manajemen Keuangan Rumah Tangga sebagai Upaya Meningkatkan Literasi Keuangan Ibu-Ibu PKK Desa Iker-Iker Geger - Nia A’inurrohmah, Afifah; Rizka Ananda Agustin, Naila; Dilla Suryani, Erika; Dwi Atikah Sari, Vira; Suwandi (Conscilience: Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
Household financial management is a crucial aspect of family life; however, many housewives lack an understanding of how to manage finances in a planned manner, resulting in expenditures that seem to run out without clear allocation. This issue is not exclusive to Iker-Iker Geger Village but is a common phenomenon among housewives in general. This community service activity was carried out by KKN Group 30 students from the Accounting Study Program of Universitas Muhammadiyah Gresik on March 28, 2026, at the Iker-Iker Geger Village Hall, targeting local PKK members. This activity explicitly aims to enhance PKK members’ understanding of household financial management, provide practical budgeting knowledge, encourage financial recording and planning habits, and foster awareness of the importance of saving and avoiding consumptive debt. The methods employed included participatory education methods through interactive discussions and joint budget simulations, as well as interactive counseling methods encompassing communicative and contextual lectures on household budgeting, visualization of budget proportion diagrams, presentation of simple financial recording tables, and prize games to sustain participant enthusiasm throughout the session. The results indicated that participants actively responded to the material, began to understand proportional budgeting concepts, and demonstrated a shift in orientation from reactive financial management toward a more planned approach. This activity is expected to provide a foundational understanding of household budgeting, enabling PKK members to manage family finances more wisely, independently, and sustainably.